Further Elucidation of the Argonaute and Dicer Protein Families in the Model Grass Species Brachypodium distachyon - Šečić, Ena; Zanini, Silvia; Kogel, Karl-Heinz (Frontiers in Plant Science, 2019)
RNA interference (RNAi) is a biological process in which small RNAs (sRNA) regulate gene silencing at the transcriptional or post-transcriptional level. The trigger for gene silencing is double-stranded RNA (dsRNA) generated from an endogenous genomic locus or a foreign source, such as a transgene or virus. In addition to regulating endogenous gene expression, RNAi provides the mechanistic basis for sRNA-mediated communication between plant hosts and interacting pathogenic microbes, known as cross-kingdom (ck)RNAi. Two core protein components, ARGONAUTE (AGO) and DICER (DCL) are central to the RNAi machinery of eukaryotes. Plants encode for several copies of AGO and DCL genes; in Arabidopsis thaliana, the AGO protein family contains 10 members and the DCL family contains four. Little is known about the conservation and specific roles of these proteins in monocotyledonous plants, which account for the most important food staples. Here we utilized in silico tools to investigate the structure and related functions of AGO and DCL proteins from the model grass Brachypodium distachyon. Based on the presence of characteristic domains, 16 BdAGO and six BdDCL predicted proteins were identified. Phylogenetic analysis showed that both protein families were expanded in Brachypodium as compared with Arabidopsis. For BdDCL proteins, both plant species contain a single copy of DCL1 and DCL4; however, Brachypodium contains two copies each of DCL2 and DCL3. Members of the BdAGO family were placed in all three functional clades of AGO proteins previously described in Arabidopsis. The greatest expansion occurred in the AtAGO1/5/10 clade, which contains nine BdAGOs (BdAGO5/6/7/9/10/11/12/15/16). The catalytic tetrad of the AGO PIWI domain, which is required for endonuclease activity is conserved in most BdAGOs, with the exception of BdAGO1, which lacks the last D/H residue. 3D modeling of BdAGO proteins using tertiary structure prediction software supported the phylogenetic classification. We also predicted a provisional interactome network for BdAGOs, their localization within the cell, and organ/tissue-specific expression. Exploring the specifics of RNAi machinery proteins in a model grass species can serve as a proxy for agronomically important cereals such as barley and wheat, where the development of RNAi-based plant protection strategies is of great interest.